Mutual trust as a backbone of EU Antitrust Law - Małgorzata Kozak (Market and Competition Law Review)
The article is an attempt to analyse to what extent a close cooperation between competition authorities belonging to the European Competition Network is based on the mutual trust principle. The fundamental importance of the principle of mutual trust was underscored in Opinion 2/13 on the Accession of the EU to the European Convention of Human Rights (ECHR), where the Court of Justice found that: “it should be noted that the principle of mutual trust between the Member States is of fundamental importance in EU law”. However, as it was emphasised by the CJEU. mutual trust does not amount to a blind trust, as it is illustrated in the case law of the CJEU in cases concerning the European Arrest Warrant. The CJEU imposes more and more obligations on executing Member States in verifying whether there are no irregularities issuing the European Arrest Warrant (EAW) in comparison to the early days of its functioning, leading towards a regulated or conditioned trust. This development mutatis mutandis is particularly interesting to analyse while referring to the functioning of cooperation of competition authorities within the EU. The research statement of this article is that based on the outcome of CJEU case law in cases concerning EAW such as e.g. Aranyosi and Căldăraru the trust in institutional cooperation such as provided by Regulation 1/2003 and Directive 2019/1 should not be blind so as not to allow the non-noticing of irregularities occurred in other Member States or before the European Commission. We will begin by framing what the concept of trust englobes and showing how it is normatively framed in EU law. Then, the analysis concentrates on where there are boundaries to mutual trust in the decentralised application of art. 101 and 102 TFEU. Subsequently, the questions of how this trust works in practice and what the boundaries are that limit its application are addressed. As the concept of mutual trust is complex itself, this article does not aim to propose detailed solutions de lege ferenda. Its ultimate objective is rather to provide a conceptual framework of de lege lata analysis of mutual trust in the application of EU competition law.